Implementation of Community-Centric Medical Education through Family Adoption Program: Descriptive Results from Coastal Karnataka - K Eshwari; Sneha D. Mallya; Ashwini Kumar; Chythra R. Rao; Akshaya Sekar; Shyamashree Das (Indian Journal of Community Medicine)
Background: National Medical Commission (NMC), in their recent notification, included Family Adoption Program (FAP) in the undergraduate curriculum to provide a learning opportunity for community-based health care to Indian Medical Graduates. Materials and Methods: As part of FAP, 1000 families living in rural areas of the district were approached. During house-to-house visits, students were accompanied by facilitators, and each student adopted four to five families from the villages. Students were trained regarding data collection tools, which included questions assessing sociodemographic characteristics, awareness, and utilization of various social security schemes. Paper-based data collection and data entry were performed using Google Forms. Geotagging of houses was conducted to facilitate follow-up visits. Results: A total of 768 households were surveyed, which included 3,238 residents with female predominance (51.9%). A significant proportion (59.9%) of the population were in the economically productive age group (20-60 years), with 38.1% educated up to secondary education (8th to 12th standard). Nearly half of respondents were aware of widow pension, Old age pension scheme, Pradhan Mantri Suraksha Bima Yojana, whereas the level of awareness was less than 50 percent for Bhagyalakshmi Scheme for girl child (44.7%) and Pradhan Mantri Jeevan Jyoti Bima Yojana (42.6%). Awareness regarding schemes for Maternal & Child Health and Disability was less, and for the Manaswini scheme, it was low. However, all the schemes were severely underutilized (28%–0.4%). The overall prevalence of any one chronic morbidity was found to be 18.4%, with hypertension and diabetes mellitus being the most common morbidities. Conclusions: FAP gives a new perspective to medical education in India by transforming existing hospital-based medical learning to a community-centered approach.